INTEGRATING THINK-PAIR-SHARE WITH OUTLINING STRATEGY IN TEACHING NARRATIVE WRITING - Virgosa, Rika Jum'a; Raja, Patuan; Flora, Flora (Universitas PGRI Sumatera Barat, 2025)
This study investigates the effectiveness of integrating the Think-Pair-Share (TPS) strategy with outlining to enhance students’ writing achievement in writing narrative text. Recognizing the difficulties EFL students face in organizing ideas and the limitations of traditional TPS methods, this study explores whether integrating outlining as a pre-writing activity can improve the quality and structure of students’ writing. A comparative analysis was conducted between students taught using TPS with outlining and those taught using the original TPS method. The study aims to determine if there is a significant difference in writing achievement between the two groups, focusing on aspects such as content, organization, vocabulary, language use, and mechanics. The findings indicate a significant improvement in writing performance among students, suggesting that integrating TPS with outlining can serve as an effective instructional strategy for improving students’ writing skills in EFL contexts.